NILAI TANGGUNG JAWAB PADA ANAK KELOMPOK B MELALUI KEGIATAN MARKET DAY DI TK MELATI HONGGOSOCO KUDUS - Dewi Apriliani; Dwi Devi Lestari; Dwi Lidia Setiyani; Siti Noor Kinanti (STPI Bina Insan Mulia Yogyakarta, 2022)
This study aims to determine the value of the responsibility of group B children in TK Melati Honggosoco Kudus through market day activities. This study uses a qualitative descriptive approach with field research methods or field research. The subject of this research is the children of group B in TK Melati Honggosoco Kudus, while the object of this research is the value of responsibility through market day activities. The results showed that through market day activities, children were able to grow an entrepreneurial spirit, one of which was the value of responsibility. This is evidenced by the task given by the researcher to group B children through market day activities that the children can complete well. During the activity, the children looked happy and enthusiastic in doing market day activities. In this market day activity, children are tasked with maintaining the bazaar by selling fruit juices and jasuke properly, serving buyers honestly and fairly, daring to accept the consequences if the goods sold are damaged before they reach the buyer. Market day activities involve parents as buyers using real money, so that children can know that money is the exchange value of goods.